Study on Risk Management of Small Foreign Trade between China and Pakistan (Global Journal of Management and Business Research, 2018)
China and Pakistan relationship has been worldwide recognized. Neighbor partners are more considered as the strategic partners since last couple of years. Day by day, both of the countries are strengthening their relationship and are engaged in number of projects that would benefit them in both, economically and growth terms. It would also result in the smoothening of the flow of relationships as well. However, there is some risk also involved with the execution of CPEC projects and other related projects well. This research paper revolves around to conduct the Study on Risk Management of Small Foreign Trade between China and Pakistan. Paper considers the adoption of qualitative research approach with the integration of positivism research philosophy. Several recent past researches have been analysed and discussed in detail. The findings have considered that there is an extensive need of integrating effective risk management in context to the small foreign trade, and focus needs to be incredibly laid on overall minimizing the risk occurrence to that maximum advantages can be extracted.